Precisiones sobre la acentuación de los nombres en -υ del griego (Minerva. Revista de Filología Clásica, 2019)
In this paper I propose a revision of the teachings about the accentuation of Gr. -υ Stems. As we observe, the accentuation differs from preclassical to classical Greek: at the beginning of the tradition the words in -υc are" not always oxytona and feminines.